Novel murine model of congenital diabetes: The insulin hyposecretion mouse. Issue 2 (17th August 2018) - Nakano, Kenta; Yanobu‐Takanashi, Rieko; Takahashi, Yuki; Sasaki, Hayato; Shimizu, Yukiko; Okamura, Tadashi; Sasaki, Nobuya
Abstract : Pancreatic perfusion with KCl elicited substantial insulin secretion in the control mice. In contrast, insulin secretion was significantly reduced in the ihs mice. These results indicated that the insulin‐secretion capability of β‐cells was markedly impaired in ihs mice. Abstract: Aims/Introduction: Diabetic animal models have made an enormous contribution to our understanding of the etiology of diabetes and the development of new medications. The aim of the present study was to develop and characterize a novel, non‐obese murine strain with spontaneous diabetes – the insulin hyposecretion ( ihs ) mouse. Materials and Methods: During the development of the ICGN.B6‐ Tns2 WT strain as the control for the ICGN‐ Tns2 nph congenital nephrotic strain, diabetic mice were discovered and named ihs mice. Intraperitoneal insulin tolerance test, oral glucose tolerance test and an insulin secretion experiment by the pancreas perfusion system were carried out on ihs mice. The pancreatic islets were examined histologically, and the mRNA expression of pancreatic β‐cell‐specific genes or genes associated with monogenic diabetes was examined by RT‐qPCR. Results: The ihs mice showed several distinctive diabetes‐related characteristics: (i) the onset of diabetes was observed only in the male mice; (ii) there were no differences in insulin content between the ihs and control mice; (iii) impaired insulin secretion was elicited by glucose, potassium chloride and sulfonylureas; (iv) there was a significant reduction of relative β‐cell volume with no signs of inflammation or fibrosis; (v) they showed a normal glycemic response to exogenous insulin; and (vi) the mice were not obese. Conclusions: The ihs mouse provides a novel murine model of congenital diabetes that shows insulin secretion failure. This model allows not only an analysis of the progression of diabetes, but also the identification of unknown genes involved in insulin secretion.